Impaired mitochondrial–endoplasmic reticulum interaction and mitophagy in Miro1-mutant neurons in Parkinson's disease. (13th April 2020) - Berenguer-Escuder, Clara; Grossmann, Dajana; Antony, Paul; Arena, Giuseppe; Wasner, Kobi; Massart, François; Jarazo, Javier; Walter, Jonas; Schwamborn, Jens C; Grünewald, Anne; Krüger, Rejko
Abstract: Mitochondrial Rho GTPase 1 (Miro1) protein is a well-known adaptor for mitochondrial transport and also regulates mitochondrial quality control and function. Furthermore, Miro1 was associated with mitochondrial-endoplasmic reticulum (ER) contact sites (MERCs), which are key regulators of cellular calcium homeostasis and the initiation of autophagy. Impairments of these mechanisms were linked to neurodegeneration in Parkinson's disease (PD). We recently revealed that PD fibroblasts harboring Miro1 mutations displayed dysregulations in MERC organization and abundance, affecting mitochondrial homeostasis and clearance. We hypothesize that mutant Miro1 impairs the function of MERCs and mitochondrial dynamics, altering neuronal homeostasis and integrity in PD. PD skin fibroblasts harboring the Miro1-R272Q mutation were differentiated into patient-derived neurons. Live-cell imaging and immunocytochemistry were used to study mitophagy and the organization and function of MERCs. Markers of autophagy or mitochondrial function were assessed by western blotting. Quantification of organelle juxtapositions revealed an increased number of MERCs in patient-derived neurons. Live-cell imaging results showed alterations of mitochondrial dynamics and increased sensitivity to calcium stress, as well as reduced mitochondrial clearance. Finally, western blot analysis indicated a blockage of the autophagy flux in Miro1-mutant neurons. Miro1-mutant neurons display altered ER-mitochondrial tethering compared with control neurons. This alteration likely interferes with proper MERC function, contributing to a defective autophagic flux and cytosolic calcium handling capacity. Moreover, mutant Miro1 affects mitochondrial dynamics in neurons, which may result in disrupted mitochondrial turnover and altered mitochondrial movement.